2018
DOI: 10.3390/ijms19113645
|View full text |Cite
|
Sign up to set email alerts
|

Cystine/Glutamate Antiporter and Aripiprazole Compensate NMDA Antagonist-Induced Dysfunction of Thalamocortical L-Glutamatergic Transmission

Abstract: To explore pathophysiology of schizophrenia, this study analyzed the regulation mechanisms that are associated with cystine/glutamate antiporter (Sxc), group-II (II-mGluR), and group-III (III-mGluR) metabotropic glutamate-receptors in thalamo-cortical glutamatergic transmission of MK801-induced model using dual-probe microdialysis. L-glutamate release in medial pre-frontal cortex (mPFC) was increased by systemic- and local mediodorsal thalamic nucleus (MDTN) administrations of MK801, but was unaffected by loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
128
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(132 citation statements)
references
References 59 publications
(125 reference statements)
3
128
1
Order By: Relevance
“…However, local administration of MK801 into the mPFC did not affect glutamate levels in the mPFC . In contrast with observations in the mPFC, inhibition of NMDAR in the MDTN induced by local administration of MK801 into the MDTN increased glutamate release in the mPFC (mPFC MK801‐induced glutamate rise) . The present study showed that perfusion of MK801 into the MDTN also increased glutamate release from the mPFC without affecting that in the MDTN.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…However, local administration of MK801 into the mPFC did not affect glutamate levels in the mPFC . In contrast with observations in the mPFC, inhibition of NMDAR in the MDTN induced by local administration of MK801 into the MDTN increased glutamate release in the mPFC (mPFC MK801‐induced glutamate rise) . The present study showed that perfusion of MK801 into the MDTN also increased glutamate release from the mPFC without affecting that in the MDTN.…”
Section: Discussioncontrasting
confidence: 93%
“…The present study showed that perfusion of MK801 into the MDTN also increased glutamate release from the mPFC without affecting that in the MDTN. These results suggest that the major mechanisms of systemic NMDAR antagonist‐induced glutamate release in the mPFC are generated by enhanced thalamocortical glutamatergic transmission outside of the mPFC …”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations